Optimization of high pressure homogenization parameters for the isolation of cellulosic nanofibers using response surface methodology - Davoudpour, Yalda (Elsevier B.V., 2015)
Response surface methodology (RSM) was used to determine the effects of high pressure homogenization (HPH) parameters (pressure and number of cycles) on the isolated yield, crystallinity, and diameter of kenaf bast cellulose nanofibers (CNF). Central composite design of experiments was utilized to determine the optimal pressure and number of cycles of HPS for the highest CNF yield, crystallinity, and lowest CNF diameter. The linear terms for the pressure and homogenization cycles had significant effects on the CNF yield, crystallinity, and diameter, whereas the interaction between the pressure and homogenization cycles had a significant effect on the CNF crystallinity. The optimized experimental conditions for the HPH process were a homogenization pressure of 56. MPa, 44 P homogenization cycles, and a 0.1. wt% fiber suspension concentration. Under these conditions, the isolated kenaf bast CNF yield was 89.9% with 56.5% CNF crystallinity and a CNF diameter of 8. nm.